Pengaruh Metode Pembelajaran Concept Mapping terhadap Motivasi dan Hasil Belajar Kognitif Siswa - Yuniatun, Baiq; Jaya, Herman (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This research was conducted at SMA Wiyata Dharma in the 2018/2019 academic year. This study aims to increase students' motivation and cognitive learning outcomes in biology subjects by using the concept mapping learning method. The type of research used in this research is quasi-experimental or quasi-experimental. The population of this study were students of class XI SMA Wiyata Dharma 2018/2019 academic year. The samples used were 39 students of class XI IPA 5 as the control class and 39 people of class XI IPA 6 as the experimental class taken with cluster random sampling technique. Data collection techniques using observation sheets and test sheets of cognitive learning outcomes. The observation sheet was given after the learning took place in the experimental class. The observation sheet aims to determine the increase in students' learning motivation. The cognitive learning outcomes test sheets are given before and after the learning process takes place, aiming to determine the increase in students' cognitive learning outcomes. Data on students' cognitive learning outcomes in this study were taken by giving pre-test and post-test to the sample class students. The test sheet used has been tested by the validator so that it can be used in this study. The results showed that the average percentage of student learning motivation in the experimental class after using the concept mapping method was 79.67 with a high motivation category. While the value of the students' cognitive learning outcomes showed that the experimental class obtained an average score of 97.43 while the control class was 98.58. The final test data of the sample class students were analyzed using t-test. based on the results of data analysis, it was obtained that tcount was 2.57 and ttable 1.46 so that tcount was greater than ttable at an error rate of 5% and dk was 76. Therefore, from the t-test analysis it can be concluded that there is a significant effect on the results. Cognitive learning of class XI SMA Wiyata Dharma students.